La mise en visibilité des eaux souterraines au Maroc : un processus historiquement lié aux politiques de développement de l’irrigation - Kévin Del Vecchio; Marcel Kuper (Développement Durable et Territoires)
Groundwater has become indispensable for agriculture in semi-arid countries and water resources are intensively exploited. Invisible for a long time, the increased physical, social, economic, territorial, and institutional visibility of groundwater is the result of a historical construction which we examine in this paper. In the case of Morocco, its visibility is linked to the strong irrigation development, fostered by the State. In connection with this, a problem of overexploitation of groundwater is now defined and put forward by the State. Despite discourses promoting the preservation of these resources, the adopted solutions reflect the historical objectives of hydraulic and agricultural policies. The current situation of groundwater overexploitation is currently redefined as a problem of a lack of water resources, justifying the implementation of new infrastructure aimed at increasing the global supply of water resources.